Aligned NMC811 electrodes by functionalized conductive graphite flakes for fast-charging Li-ion battery - Kang Yang; Yilan Jiang; Chun Huang (Next Energy, 2024)
In recent years, the demand for high capacity, long cycle life, fast charging, and increased safety lithium-ion batteries has become increasingly urgent, especially in the electric vehicle industry. The specific capacity of Li-ion batteries is growing steadily under the great efforts of researchers. However, fast charging, as one of the key technologies of lithium-ion batteries, is still not fully and efficiently resolved. Electric vehicles now have a sufficient driving range, but they take too long to refill compared to traditional vehicles. Here, we aligned polycrystalline NMC 811 microparticles by functionalized graphitic flakes (conductive graphite KS6) under a rotating magnetic field by 2 steps in the cathode fabrication process and constructed an effective and fast conducting three-dimensional conductive network for both electron and ion transport in the cathode system of a high-rate performance Li-ion battery. We successfully regulate and control the tortuosity and porosity of the NMC811 cathode on the electrode level. The new electrode structure has higher ionic conductivity and higher specific capacity. The specific capacity of the electrode with the new electrode structure is about four times and five times the reference electrode at 5 C and at 10 C, respectively. And, the half-cell of the electrode can be fed with 70 % SOC in a 6-min charge at 5 C.